Perlindungan Hukum Pembajakan Film Digital: (Studi Perbandingan Hukum Indonesia, Malaysia, dan Korea Selatan) - Reviansyah Erlianto; Hana Faridah (Universitas Serang Raya, 2022)
Cinematography is one of the copyrighted works that are included in the scope of works that are protected in the Copyright Law, therefore the state needs to protect film works, especially domestic films. In the case of rampant acts of digital film piracy, resulting in moral and economic losses to the creators or filmmakers, of course the need for legal protection by the state for them. The purpose of this study is to understand the existence of the state in copyright protection related to the phenomenon of film piracy, and to compare regulations related to copyright between Indonesia, Malaysia, and South Korea. The author conducts legal comparisons and uses normative legal research methods in the form of secondary data that are combined through a literature study. The results obtained are that the three countries through their respective regulations regulate and protect all forms of creation produced through IPR. And the need for the government's role in educating the public in appreciating copyright and copyrighted works.